The relationship between serum ammonia level and neurologic complications in patients with acute glufosinate ammonium poisoning: A prospective observational study. (June 2018) - Cha, YS; Kim, H; Lee, Y; Choi, EH; Kim, HI; Kim, OH; Cha, K-C; Lee, KH; Hwang, SO
Glufosinate ammonium poisoning can cause neurological complications even after a symptom-free period. We prospectively investigated the predictors of neurologic complications in acute glufosinate ammonium poisoning and the change of serum ammonia level as a predictor of patient's presence and recovery of neurologic complication. This prospective observational study collected data from consecutive patients diagnosed with acute glufosinate ammonium poisoning between September 2014 and June 2016. Serum ammonia was serially measured. The patients were divided into two groups: the neurologic complication group and the nonneurologic complication group. We also defined 25 other insecticide- or herbicide-poisoned patients as controls. The neurologic complication group included 18 patients (72.0%). The latency period for neurologic complications was within 48-h postingestion. The peak ammonia level was statistically higher in the neurologic complication group than in the control group ( p < 0.001) and the nonneurologic complication groups ( p = 0.001). There was a statistical difference between the nonneurologic complication group and the neurologic complication group ( p = 0.0085) in terms of ingested amount. The peak ammonia was the only predictor for the development of neurologic complications (the optimal cutoff: 90 μg/dL). In patients with mental changes, the mean serum ammonia levels before and after recovery of the mental changes were statistically different ( p = 0.0019). In acute glufosinate ammonium poisoning, serial serum ammonia level measurements are needed and a serum peak ammonia level greater than 90 μg/dL is a predictor of neurologic complications. Also, it is important to treat the hyperammonemia in acute glufosinate ammonium poisoning.